MADRASAH AND PARENTS ALLIANCE AS AN EFFORT TO PREVENT INVISIBLE TEACHERS - Astutik, Ummi Puji; Fauzan, Umar; Malihah, Noor (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2023)
The purpose of this study was to reveal how the collaboration of madrasas and parents as an alliance prevents invisible teachers from occurring in the MTs environment. Raudlatus Sholihin. This research method used a qualitative case study type. MAN 2 Samarinda was the location and object of this research. Data collection techniques used observation, interviews with 6 informants (head of madrasah, Deputy Head of Public Relations, Deputy Head of Curriculum, one of the class teachers, and 2 parents of students), and documentation. The analysis technique applied the interactive analytical model of Miles, Huberman, and Saldana by condensing the data, presenting the data, which then draws conclusions. Source triangulation was a technique for checking the validity of data. The results of the study explained that the alliance of madrasah cooperative relations with parents can be an influence on preventing invisible teachers of MAN 2 Samarinda. There were two efforts in this regard, namely volunteering in community groups and routine weekly work meetings using brainstorming techniques. As a member of the community, the teacher acts as a role model for the community around him, both in his personal life and family life. As a community agent, the teacher acts as a mediator between the community and the world of education in schools.